Upaya Pengurangan Limbah Kemasan Plastik Air Minum Melalui Kajian Kualitas Keran Air Siap Minum (KASM) di Wilayah Kota Bogor - Iryani, Ani; Syahputri, Yulian; Ramadhini, Dania; Purnama, Dicky Budhi (LPPM Universitas Mataram, 2024)
Sales of bottled drinking water (AMDK) increase in line with population growth every year. Based on data from the Indonesian Plastic Industry Association (Inaplas) and BPS, Indonesia produces 64 million tons of waste/year, and 3.2 million tons of plastic waste comes from AMDK. In connection with the community's dependence on consuming AMDK, the government through the Regional Public Company (PERUMDA) Tirta Pakuan created a superior program, namely Tap Water Ready to Drink (KASM). The problem is that many residents do not take advantage of KASM's services. The aim of this research is to compare the quality of AMDK and KASM so that the public can obtain information and increase confidence in the quality, safety and cleanliness of drinking water originating from KASM. This research method includes sampling followed by analysis of physical parameters (color, odor, taste, temperature), chemical (turbidity, TDS, metals, pH, Cl-, F-, NO2-, NO3-, NH3, hardness, CN -, SO42-) and Total microbiology (Coliform, E.coli) based on quality standards PERMENKES 492/2010. KASM samples were taken at 6 points using the SNI 8995:2021 method. The AMDK sample was obtained by purchasing 5 brands of AMDK randomly. Physical, chemical and microbiological parameters were analyzed using the APHA, SNI, US-EPA methods using ICP-OES, UV-Vis spectrophotometer and nephelometer. The results show that all KASM and AMDK samples have met the quality standards of PERMENKES 492/2010. Based on the comparison of analysis results, all AMDK samples had lower quality compared to KASM samples even though other microbiological, chemical and physical parameters were not significantly different.